The prescription pattern of initial treatment for type 2 diabetes in Beijing from 2011 to 2015. Issue 8 (February 2019) - Wang, Xiaowen; Cao, Yaying; Wu, Yao; Yang, Chao; Song, Jing; Tian, Yaohua; Wang, Mengying; Li, Man; Wu, Yiqun; Hu, Yonghua
Abstract : Abstract: The purpose of this study was to describe the prescription pattern of initial treatment for type 2 diabetes (T2DM) in Beijing from 2011 to 2015. We selected 790, 339 newly diagnosed outpatients with T2DM from the Beijing Medical Claim Data for Employees database between January 2011 and December 2015. The percentages of different treatments and agents were calculated from the patients' 1st prescriptions. Subgroup analyses were conducted for primary, secondary, and tertiary hospital settings. The initial treatments given to 57.7%, 30.7%, and 11.7% of patients were oral hypoglycemic agent (OHA) monotherapy, OHA polytherapy, and insulin, respectively. Alpha-glucosidase inhibitors (AGIs) (43.0%) were the most commonly used agents for monotherapy, followed by metformin (35.5%) and sulfonylureas (14.9%). AGIs were most commonly used in primary hospitals (52.0%), while metformin was prescribed most often in secondary (37.6%) and tertiary (41.8%) hospitals. From 2011 to 2015, there were increases in the use of AGIs (40.1–41.1%, P < .001) and metformin (34.0–40.4%, P < .001), but a decrease in the use of sulfonylureas (18.1–12.8%, P < .001). Similar trends were seen in the different hospital settings. Metformin plus an AGI, a sulfonylurea plus an AGI, and metformin plus a sulfonylurea were the most common OHA polytherapy combinations. The use of metformin plus an AGI increased from 13.8% in 2011 to 19.7% in 2015 ( P < .001), while the use of a sulfonylurea plus an AGI, and metformin plus a sulfonylurea, did not change significantly. Half of newly diagnosed patients with T2DM received an initial treatment of OHA monotherapy. Although the use of metformin increased from 2011 to 2015, both AGIs and metformin were the most commonly prescribed agents. The patterns differed from those of most other countries and identification of the underlying reasons will require further investigation. Abstract : Supplemental Digital Content is available in the text